Seismic behaviour of Masonry structures retrofitted with GFRP - Rathnasheela, P.T.; Senthil, R. (Journal of Structural Engineering, 2024)
Brick masonry suffers damage during earthquakes. In the Bhuij Earthquake, majority of the masonry structures were damaged because they were built with un-reinforced masonry (URM)¹. The code of practice for brick masonry IS 4326-1993 suggests the use of lintel band to integrate the structure and thus introduce a rigid box like behaviour². Though the code recommendations are based on the experiments done elsewhere, the problem is still a complex one because each type of building is unique in construction features like different ratio of binder to sand used in mortar, thickness of mortar and provision of openings, etc. Un-reinforced masonry structures are prone to extensive damage followed by failure and collapse when subjected to loads resulting from wind, earthquake and other natural or man-made events. Recent earthquakes and terrorist acts have clearly demonstrated that the development of effective and affordable strategies for the strengthening of masonry is urgently needed. But in the recent past GFRP (Glass Fiber Reinforced Polymer) is found to be an alternative modern technique used to strengthen the masonry elements. In the present study the behaviour of simple masonry elements with and without GFRP wrappings subjected to base shock vibrations for out-of-plane loadings is carried out. Based on the experimental investigation, the failure pattern and energy dissipation capacity of the masonry elements with and without GFRP wrappings is estimated. The masonry elements were instrumented with data acquisition systems.